kokol111
15

# Przy danych a) P (A') = 1/2 P (A u B) = 2/3 P (A razy B) = 1/3 oblicz : P( B) P (A\B) P (B/A) b) P (B')=3/4 P (A u B) = 1/3 P (A razy B) = 1/5 Oblicz: P(A') P (A\B) P (B/A) Powoli, spokojnie, dokładnie poproszę :)

(2) Odpowiedź
anna21144

a) P(A)=1-P(A') P(A)=1-1/2=1/2 P(AuB)=P(A)+P(B)-P(AnB) P(B)=P(AuB)+P(AnB)-P(A) P(B)=2/3+1/3-1/2=1-1/2=1/2 P(B)=1/2 b) P(B)=1-3/4=1/4 P(A)=P(AuB)+P(AnB)-P(B) P(A)=1/3+1/5-1/4=20/60+12/60-15/60=17/60 P(A')=1-17/60=43/60 P(A\B)=P(A)-P(AnB) P(A\B)=17/60-1/5=17/60-12/60=5/60=1/12 P(B/A)=P(AnB)/P(A) P(B/A)=1/5 : 17/60=1/5*60/17=12/17

andzia17

[latex]P(A)=1-P(A') [/latex] [latex]P(A)=1-1/2=1/2 P(AuB)=[/latex] [latex]P(A)+P(B)-P(AnB)[/latex]   [latex]P(B)=P(AuB)+P(AnB)-P(A) [/latex] [latex]P(B)=2/3+1/3-1/2=1-1/2=1/2[/latex] [latex] P(B)=1/2[/latex] ----------------------------------------------------------------------------------------------- [latex]P(B)=1-3/4=1/4[/latex] [latex]P(A)=P(AuB)+P(AnB)-P(B)[/latex] [latex]P(A)=1/3+1/5-1/4=20/60+12/60-15/60=17/60[/latex] [latex]P(A')=1-17/60=43/60[/latex] [latex]P(A\B)=P(A)-P(AnB)[/latex] [latex]P(A\B)=17/60-1/5=17/60-12/60=5/60=1/12[/latex] [latex]P(B/A)=P(AnB)/P(A)[/latex] [latex]P(B/A)=1/5 : 17/60=1/5*60/17=12/17[/latex]

Dodaj swoją odpowiedź